Mobile rfid tracking system : software architecture - M.Syahrul Faiz, Abd Manan (Universiti Malaysia Sarawak, UNIMAS, 2010)
This project presents the design of a Mobile RFID Tracking System. It is designed to track an object in wide area for example a moving children in Electronics Engineering’s building using RFID technology. This system using radio frequency identification (RFID) can be divided to hardware and software part. In this study, only software part is being researched and developed. Software system can be analogy as a central processor and hardware part as controlled devices. This preliminary project will focus on software development using Visual Basic 6 that provides user with a way to interact with the system, user friendly, comfort and interactive for the users. Users can easily monitor the position of tagged children in a large distance by implementing an application that reveals the position of a children at anytime anywhere in the coverage area. Currently, many of children missing cases happened every day. A lot of initiative to prevent these problems including the installation of the surveillance camera and Global Positioning System (GPS) tracker in potential problem areas. However, the surveillance camera has it blind area that makes it useless to track the object in critical angle and GPS is ineffective indoors because buildings block GPS transmission but RFID is more reliable because radio signal can penetrate any obstructions and it is very cheap compared with surveillance camera and GPS. In conclusion, this system has the high market potential. From this project, the system has been successfully developed that contains RFID Tags Registry form, graphic user interface (GUI) design, vii communication module (master), communication module (slave) and database that detect location of the object within each m